BIOCHEMICAL STUDIES OF HIPPOCAMPAL GENE EXPRESSION OF BRAIN-DERIVED NEUROTROPIC FACTOR AND TOLL-LIKE RECEPTOR-4 IN DIABETIC RATS EXPOSED TO CHRONIC STRESS: EFFECTS OF ANTIDEPRESSANT DRUGS - Aboul-fotouh, Sawsan; Hassan, Doaa; Habib, Mohamed; Amin, Ahmed Ibrahim; Kassim, Samar Kamal; Mohamed, Amr Saad (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Â Objective: Depression and diabetes are closely associated in a reciprocal manner, leading to significant morbidity and mortality with an evidence of a pro-inflammatory state underlying pathophysiology of both diseases. Unfortunately, little information is available about the effects of antidepressant drugs on hippocampal brain-derived neurotrophic factor (BDNF) and toll-like receptor-4 (TLR-4) expression in diabetes. Methods: We investigated the effect of chronic administration of fluoxetine (FLU) and imipramine (IMIP) on behavioral, metabolic, and inflammatory abnormalities in diabetic and non-diabetic rats exposed to chronic restraint stress (CRS). Results: Both diabetes and CRS induced depressive-like behavior which was more prominent in diabetic/depressed rats; this was reversed by chronic treatment with FLU and IMIP. Diabetic and non-diabetic rats exposed to CRS showed a significant increase in hippocampal expression of TLR-4 and pro-inflammatory cytokines alongside a decrease in BDNF expression. FLU and IMIP ameliorated these inflammatory abnormalities. Conclusion: Diabetes mellitus (DM) and chronic stress induced a depressive-like behavior associated with an increase in hippocampal expression of TLR-4, tumor necrosis factor-Î±, and interleukin-1ÃŸ with a significant correlation to decreased BDNF expression. FLU and IMIP showed comparable effects regards the improvement of depressive and inflammatory abnormalities associated with DM.